And the award goes to... - Morrison, Keith (Macau Business, 2022)
Macau, MNA, Opinion | The Macau government recently approved its first reading of a new bill to attract Macau locals to return to Macau to work. Simultaneously, Macau’s Secretary for Social Affairs and Culture was reported as saying that if Macau could create a better environment and conditions, then ‘local talents who are abroad will surely be interested in returning to Macau’.
Section: MNA